Antioxidant Activity of Garcinia cf bancana Miq - Hartati, Sri; Triyem, .; Cahyana, Herry (Indonesian Research Gateway, 2010)
Guttiferron F and essential oil were isolated from extractÃÂ n-hexane ofÃÂ Garcinia cf bancanaÃÂ Miq. Antioxidant activity was done by DPPH method toÃÂ ÃÂ n-hexane, methanol, ethyl acetate, n-butanol extracts and Guttiferron F, showed activity with IC50 24.5, 22.4, 29.2, 37.6 and 25.8 ÃÂµg/mL respectively. The structure elucidation of Guttiferon FÃÂ based on spectroscopy data of IR, NMR of 1H and 13C.